Leading Class Program Evaluation in Improving the Quality of Education - Aulya Fahma; Mesiono Mesiono; Yusuf Hadijaya (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This article aims to analyze the evaluation of the unique class program's context, input, process, and output in improving the quality of education. The research was conducted at Madrasah Tsanawiyah Muallimin UNIVA Medan. The research uses the CIPP Model, namely Context, Input, Process, and Product. Furthermore, data validity uses the level of trust, switchability, dependability, and confirmability, which refers to Moleong. The results of the research show that the program context, program inputs, program processes are considered good because they are efforts made by Madrasas in improving the quality of education. In addition, based on the program evaluation conducted, the quality of madrasas showed their effectiveness in a reasonably good category. Therefore, research recommends that other madrasahs in Indonesia improve their education quality by implementing a unique class program because it has been proven effective in improving the quality of madrasa education